ADOPSI KERANGKA KERJA ITIL 3.0 UNTUK PERANCANGAN MANAJEMEN LAYANAN SI/TI PADA PERUSAHAAN MANUFAKTUR (STUDI KASUS : PT XYZ) - Setiyono, Natasha Christita; Kurniawan, Yudhi (Universitas Ma Chung, 2024)
PT XYZ is a company engaged in manufacturing land transportation and other land facilities. Currently the company is trying to manage, improve, and implement information technology-based business services in order to provide the best service and in accordance with the principles of good corporate governance. Although the company has sufficient information technology support, there is still a lot of information technology governance that must be documented, and the use of information technology services is not running optimally. Therefore, the focus of this research is to design IS/IT service management based on the company's internal business processes so that recommendations for implementing information technology service management are produced. The method used in this research uses the third version of the Information Technology Infrastructure Library (ITIL) with the Service Strategy and Service Design domain areas. The research flow is designed based on the processes in each of these domains. In addition, an analysis of the business processes owned by the company was also carried out before they were defined into the two domain areas. The results of the analysis of business processes in the service strategy and service design domains obtained several proposals for information technology services and designs that can be used in the future to optimize the achievement of the implementation of the use of IT services in running the company's business processes.